Role of zoological research in sustainable development (Zoological Records and Reviews, 2025)
Zoological research -- encompassing systematic taxonomy, population ecology, behavioural science, conservationbiology, and wildlife management -- contributes to sustainable development through multiple pathways: providing thebiodiversity knowledge base essential for ecosystem service valuation and natural capital accounting; informingwildlife-based economic sectors (ecotourism, sustainable fisheries, pollination services); enabling zoonotic diseasesurveillance and pandemic prevention through wildlife health monitoring; supporting food security through insectpollinator conservation and biological pest control research; and generating the evidence base for biodiversity-inclusiveland use planning and environmental impact assessment. This review synthesises evidence from 186 primary studies(2005-2025) examining the contributions of zoological research to eight Sustainable Development Goals (SDGs) -- SDG2 (Zero Hunger), SDG 3 (Good Health), SDG 8 (Decent Work), SDG 11 (Sustainable Cities), SDG 13 (Climate Action),SDG 14 (Life Below Water), SDG 15 (Life on Land), and SDG 17 (Partnerships) -- quantifying economic and socialco-benefits where evidence is available. Zoological research most directly contributes to SDG 15 (composite contributionscore 2.72/3.0) and SDG 14 (2.48), but significant contributions to SDG 2 (pollinator and pest control research: estimatedEUR 153 billion/year European economic value) and SDG 3 (zoonotic disease surveillance: 60% of emerging infectiousdiseases are zoonotic) are frequently undervalued in research impact assessments. A framework for aligning zoologicalresearch priorities with SDG targets and EU Biodiversity Strategy 2030 commitments is presented.